Perbedaan Kadar Caffeic Acid Phenethyl Ester antara Propolis yang Diekstraksi dengan Etanol dan Air - Riani Dwi Hastuti; Diding HP; Sri Hartati (Nexus Biomedika, 2013)
Background: Propolis is a natural product derived from plant resins which is collected by honeybees. One of the major components of propolis is Caffeic Acid Phenethyl Ester (CAPE). The use of various kinds of solvents in propolis extraction effects CAPE level. The aim of this research was to know the difference levels of CAPE in ethanol extract propolis and water extract propolis. Methods: This study was experimental research with post test only group design. Samples were raw propolis taken from bee farm in Gejen RT 03 RW 02, Kerjo, Karanganyar. Samples were extracted with maceration method using ethanol and water as solvents. Both of ethanol extract propolis and water extract propolis were divided into five samples. CAPE levels were determined by UV Vis spectrophotometer at wave length of 700 nm using Prussian Blue method. Data were analyzed using independent sample t test. Results: The result showed that the average of CAPE level in propolis extracted with ethanol was 12.26 0.658 g/mL, while the average of CAPE level in propolis extracted with water was 5.564 0.332 g/mL. Conclusions: There was no significant difference between propolis extracted with ethanol and water. Keywords: CAPE, ethanol extract propolis, water extract propolis.